Applying “Men and Women for Others” to Writing about Archeology - Karen Surman Paley (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
This essay explores one archeology professor's pedagogy of caring during a summer field study of a former state school and orphanage.